Determinant Of Investment Decision With Growth Opportunity As Moderation Variable: Study On Sub-Sector Textile And Garmen Companies Listed On The Indonesian Stock Exchange - Putu Eka Maharani; Ni Luh Putu Wiagustini (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
An investment decision is a plan to invest in one or more assets in hopes of generating future returns. Investment decisions aim to obtain profits in the future with a certain level of risk and can maximize the prosperity of the owners (shareholders). The purpose of this study is to analyze the influence of capital structure, liquidity, profitability, and company size on investment decisions with growth opportunities as moderation variables in textile and garment sub-sector companies listed on the Indonesia Stock Exchange. This research was conducted on textile and garment sub-sector companies listed on the Indonesia Stock Exchange with a sample of 14 companies using saturated sampling techniques. Financial statement data is collected from the Indonesia Stock Exchange website and the websites of the companies sampled. The collected data is then analyzed with Moderated Regression Analysis (MRA). The results showed that capital structure has no effect on investment decisions, liquidity has no effect on investment decisions, profitability has a negative effect on investment decisions, company size has no effect on investment decisions, growth opportunities moderate the relationship of capital structure and profitability on investment decisions and growth opportunities cannot moderate the relationship between liquidity and company size on decisions investment. Keywords: Investment Decision, Capital Structure, Liquidity, Profitability, Firm Size